EXTENDING THE SHELF-LIFE OF WHEAT BREAD USING PENTOSANES EXTRACTED FROM BARLEY - R. G. Nashmi; J. M. Naser (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This research was aimed to delay the staling of wheat bread as one of the most used products globally by adding barley pentosanes, which is neglected and not taken into consideration despite their unique and multiple functional properties and their optimum storage temperature. Water-soluble pentosanes (WSP) and water-insoluble pentosanes (WIP)was extracted from barley (Hordeum vulgare) and added to wheat flour at different percentages. Five treatments were prepared: (T1) from flour only, (T2 and T3) adding WSP at levels of (1 and 2%), (T4 and T5) adding WIP at the same levels respectively. All treatments were stored at (20, 4 and -18 °C), for 72 h. The results indicated that the addition of pentosans (WSP and WIP) delayed the staling of bread, especially at the level of addition (2%) for both, when was stored at freezing temperature (-18°C). The results of the control treatment (T1) and the treatments that included the highest addition level (2%) ( T3 and T5) and after 72 hours of storage at (-18°C) were as follows: The moisture content of bread crumbs decreased to (39.44, 43.32 and 43.91%) respectively. While the moisture in the bread crust increased to (31.61, 33.98, 34.28%), respectively. The swelling power of the bread crumbs and the sediment volume also decreased to (0.74, 1.18, and 1.03%) and (23, 32 and 33%), respectively, which indicates the potency of pentosans and freezing temperature to delay the staling of wheat bread during the storage period.